The influence of leadership style on employee performance through work motivation at the secretariat of Simeulue Regency - Ahmadlyah, Ahmadlyah; Hasyim, Hasyim; Nadia, Lula (Universitas Wiralodra, 2024)
This study examines the effect of leadership style on employee performance at the Regional Secretariat of Simeulue Regency through work motivation. This study used a quantitative approach, involving 85 respondents from various units in the Secretariat. Data were collected through questionnaires covering leadership style, work motivation, and employee performance. The data that has been collected is then analyzed using a regression test with the help of the SPSS statistical program. The results of the statistical analysis show that leadership style does not significantly influence employee performance (t=1.600, sig=0.114). However, leadership style positively and significantly influences work motivation (t=4.879, sig=0.000). Work motivation, in turn, has a positive and significant impact on employee performance (t=2.609, sig=0.011). Path analysis and the Sobel test support that work motivation mediates between leadership style and employee performance. These results make an important contribution to the practical and theoretical understanding of how leadership style can influence employee performance through the mediating variable of work motivation in the local government context. Practical recommendations include developing management strategies that emphasize developing management strategies that emphasize improving work motivation, taking into account the aspects of leadership style identified in this study. This research provides a basis for further discussion and corrective action to improve leadership effectiveness and organizational performance in the Regional Secretariat of Simeulue Regency.